Analisis EMP Indonesia dan Empat Negara ASEAN pada Masa Krisis - Sulaeman, Clara Septyana Rahma; Lisna, Vera (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
Contagion effect or domino effect which causes spreading economic crisis from one country to another also occurred in Indonesia in 1997 and 2008. The e ect was identified by Exchange Market Pressure (EMP) index which measures economic pressure faced by a country on the exchange market through foreign exchange rate changes and foreign exchange reserves. The results of EMP analysis in Indonesia and four ASEAN countries using VAR method show that EMP contribution of four ASEAN countries in 2008 was larger than that of 1997. Moreover, the 1997 crisis in Indonesia spread from Thailand, while the 2008 crisis spread from Singapore.